Implementation of the Job Creation Law on the Supervisory Function of Foreign Workers by the Manpower and Transmigration Service - Massi, Randy Atma R.; Mursyid, Besse Tenriabeng (Jurusan Hukum Tatanegara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin, 2023)
The phenomenon of the high number of foreign workers (TKA), which is increasing every year in Indonesia, especially in the Central Sulawesi region, of course, means that the supervisory function carried out by the Central Sulawesi Province Manpower and Transmigration Service will be increasingly strict. However, since the existence of the Job Creation Law, employment agencies have changed the supervisory function of TKA. The research aims to analyze the role of the employment service in carrying out the supervisory function of foreign workers entering the Central Sulawesi region after the existence of the Job Creation Law. The research method used in this research is Normative Juridical research, which will examine the role of the employment department's supervisory function from changed aspects of the Job Creation Law. To examine how the law should apply. where based on cases in the field, researchs try to analyze facts and also applicable legislation. The research results show that the supervisory function of the Manpower Service after the existence of the Job Creation Law still provides a mandate similar to the Manpower Law. However, in its implementation, as an institution appointed by the state that has the task and function of issuing IMTA (Permits to Employ Foreign Workers), it has now been revoked by the Job Creation Law. The regulations regarding foreign workers after enacting the Job Creation Law underwent significant changes. Keywords: Employment Service; Supervisory Function; Job Creation Law